Beyond Fertilizer and Seed Subsidies: Rethinking Support to Incentivize Productivity and Drive Competition in Agricultural Input Markets - Aditya Alta; Indra Setiawan; Azizah Nazzala Fauzi (Center for Indonesian Policy Studies (CIPS), 2021)
Agriculture inputs are among the key factors behind agricultural productivity. Many problems, however, still plague policies on agricultural inputs for Indonesian farmers. One is the subsidized fertilizer program, which has turned out to cause a number of problems such as overconsumption of chemical fertilizers, frequent shortages, farmers prioritizing cost factors over land needs, limited choices, and of course the ever swelling subsidy budget. This paper makes a number of recommendations for increasing agricultural productivity and a fully transitioning to market mechanisms in the agricultural input sector, for more prosperous farmers and a more developed Indonesian agriculture.
Keywords: 330; Agricultural productivity; agriculture; food security; cips policy papers; food security and agriculture; agricultural policy; fertilizer subsidies; seed subsidies; agricultural inputs; agriculture inputs indonesia; organic fertilizers; agricultural input markets; agricultural market mechanisms; farmer entrepreneurship; seed programs; Indonesian fertilizers; agricultural programs; aditya alta; agricultural policy papers; farmer welfare; Indonesia's fertilizer subsidy programs; access to quality agricultural inputs; chemical fertilizersin indonesia; Indonesia agriculture policy; Indonesia agriculture; Indonesian farmers